Charismatic political leadership and Tun Dr Mahathir Mohamad's Malaysia: power, control, stability and defence - Temiz, Suleyman; Islam, Arshad (IIUM Press, International Islamic University Malaysia, 2019)
Prior to his renewed incumbency, as the fourth Prime Minister of Malaysia, Mahathir Mohamad (b. 1925) was able to remain in power for a more prolonged period compared to his predecessors. He was actively involved in galvanizing political action immediately after the independence of Malaysia and did not abandon active politics until his 2003 resignation. Under Mahathir's leadership and guidance, Malaysia made remarkable economic and political progress. He oversaw many innovations in the fledgling democracy and was able to develop the country due to his exceptional leadership qualities. His style and attitude towards engaging with problems, particularly his stance during the Asian Monetary Crisis in 1997, was highly criticized by some, and labelled as dictatorial. This stigma did not detract him from the path he considered right for Malaysia, and under his leadership he garnered worldwide appreciation for his national efforts and success in overcoming the economic crisis. Mahathir is undeniably an excellent case study as a prime minister, as well as a highly productive person. He contributed to a better understanding of modern Malaysia and his own tenure as PM in a series of books and articles. One of the significant aspects of his political heritage is his influential charisma and leadership. In all of his undertakings he has attracted both passionate support and hatred from friends and foes, but his political footsteps have always been certain and directed toward Malaysia's national wellbeing. Mahathir is a politician with sharp views on many issues and he was profoundly brave in verbalising them in the public arena, within Malaysia and internationally. His clear posture and speeches without fear made him a world-embracing political personality. This descriptive research study adopts a qualitative approach to analyse historical information, documents, memoirs and articles, and books to better understand the leadership of Mahathir. Copyright © IIUM Press.